The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1091/mbc.e20-01-0026
|View full text |Cite
|
Sign up to set email alerts
|

DYRK kinase Pom1 drives F-BAR protein Cdc15 from the membrane to promote medial division

Abstract: Phosphorylation by the DYRK kinase Pom1 is one of two major signals for proper division site placement in Schizosaccharomyces pombe. Pom1 phosphorylation of F-BAR protein Cdc15 inhibits its membrane and protein binding, thus inhibiting scaffolding of the cytokinetic ring and preventing mislocalized division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(88 citation statements)
references
References 57 publications
(98 reference statements)
9
79
0
Order By: Relevance
“…The full role of Pak1 in cytokinesis likely involves proteins beyond Mid1, consistent with our identification of Cdc15, Cyk3, and Rng10 as new substrates for Pak1. We note that Cdc15 and Cyk3 are also phosphorylated by the cell polarity kinases Pom1 and Kin1 ( Kettenbach et al, 2015 ; Lee et al, 2018 ; Bhattacharjee et al, 2020 ), and Pom1 further phosphorylates the Rng10 ligand Rga7 ( Kettenbach et al, 2015 ). Put together, these connections reveal a strong and growing role for cell polarity signaling in the regulation of CAR proteins for cytokinesis.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The full role of Pak1 in cytokinesis likely involves proteins beyond Mid1, consistent with our identification of Cdc15, Cyk3, and Rng10 as new substrates for Pak1. We note that Cdc15 and Cyk3 are also phosphorylated by the cell polarity kinases Pom1 and Kin1 ( Kettenbach et al, 2015 ; Lee et al, 2018 ; Bhattacharjee et al, 2020 ), and Pom1 further phosphorylates the Rng10 ligand Rga7 ( Kettenbach et al, 2015 ). Put together, these connections reveal a strong and growing role for cell polarity signaling in the regulation of CAR proteins for cytokinesis.…”
Section: Resultsmentioning
confidence: 92%
“…We focused on the new Pak1 substrates Cdc15 and Mid1 due to their roles in cytokinesis. Cdc15 is a membrane-binding phosphoprotein that connects multiple cytokinesis factors to the CAR ( Roberts-Galbraith et al, 2010 ; Martín-García et al, 2014 ; Kettenbach et al, 2015 ; Ren et al, 2015 ; Willet et al, 2015 ; Lee et al, 2018 , Bhattacharjee et al, 2020 ) and exhibits synthetic genetic defects with pak1 mutations ( Fig. 4, A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cdc15 is a crucial structural scaffold protein and is known to be cell cycle regulated (Fankhauser et al, 1995;Swaffer et al, 2018). It was previously indicated that Cdc15 localization and function during the early stages of AMR assembly might be regulated through de-/ phosphorylation of its unstructured region and SH3 domain by the septation initiation network (SIN) and Pom1, respectively (Figure 3A; (Fankhauser et al, 1995;Wachtler et al, 2006;Roberts-Galbraith et al, 2010;Mcdonald et al, 2015;Bhattacharjee et al, 2020). However, the exact function of the posttranslational modification dependent regulation of Cdc15 structure during cytokinesis is not fully understood yet.…”
Section: Mapping Changes In Protein Mobility During Formation and Contraction Of The Actomyosin Ringmentioning
confidence: 99%
“…Additionally, we included the truncated version of Cdc15 lacking its SH3 domain in our experiment (Roberts-Galbraith et al, 2009). The Cdc15 SH3 domain is known to recruit proline-rich (PxxP) motifcontaining proteins (such as Pxl1 and Fic1) to the AMR (Roberts-Galbraith et al, 2009;Ren et al, 2015;Bhattacharjee et al, 2020) and thus is expected to play an important role in the formation of the AMR.…”
Section: Mapping Changes In Protein Mobility During Formation and Contraction Of The Actomyosin Ringmentioning
confidence: 99%